Strategic management in the public sector - Paul Joyce (London ; New York Routledge, 2015)
"Strategic management is widely seen as essential to the public services, leading to better performance and better outcomes for the public. In fact, the private sector idea of strategic management has become so powerful in the public sector that politicians and policy makers have begun to talk about the importance of the modern state being strategic--and we may be witnessing the emergence of the Strategic State.Strategic Management for the Public Sector draws on experience and research from a range of countries and provides a theoretical understanding of strategic management that is grounded in the public sector. Drawing on the latest theory and research this text provides a fresh look at foresight, analysis, strategic choice, implementation and evaluation. This book also offers original and detailed case studies based on up to date evidence from different public sector settings, helping the reader to build on their understanding of theories and concepts presented earlier in the book.Strategic Management for the Public Sector has been written specially for managers and students taking postgraduate courses such as MBAs and MPAs. It will also appeal to individual managers and civil servants in the public sector looking for an accessible book to read as part of their own independent personal development. "-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Public administration